Artcamp Hakushu '94. : Open-Air Art Installations. (Tokyo : Artcamp Hakushu Executive Committee, 1994)
Ebizuka, Koichi ; Endo Toshikatsu ; Enokura, Koji ; Etsukawa, Osami ; Fujimura, Katsuhiro ; Fujiwara, Shun ; Fukuda, Atsuo ; Fukuda, Yukio ; Haraguchi, Noriyuki ; Hayashi, Takeshi ; Hoshina, Toyomi ; Ikegaya, Hajime ; Kenmochi, Kazuo ; Kobayashi, Rifu ; Koyama, Hotaro ; Kulve, Henk Ter ; Muraoka Saburo ; Sakaguchi, Hirotoshi ; Sasaki, Hiroaki ; Sato, Cihiro ; Sato, Tokihiro ; Takayama, Noboru ; Tanaka, Keisuke ; Torao, Yutaka ; Tsubo, Ryoichi ; Tsuji, Ko ; Yamamoto, Eishi ; Yanai, Tsuguo
Summer Art Festival Hakushu '94, August 25-28, 1994
English-Japanese
kunstcatalogus